An In Vitro Comparison of the Marginal Adaptation Accuracy of CAD/CAM Restorations Using Different Impression Systems. Issue 7 (8th February 2016) - Shembesh, Marwa; Ali, Ala; Finkelman, Matthew; Weber, Hans‐Peter; Zandparsa, Roya
Abstract: Purpose: To compare the marginal adaptation of 3‐unit zirconia fixed dental prostheses (FDPs) obtained from intraoral digital scanners (Lava True Definition, Cadent iTero), scanning of a conventional silicone impression, and the resulting master cast with an extraoral scanner (3Shape lab scanner). Materials and Methods: One reference model was fabricated from intact, non‐carious, unrestored human mandibular left first premolar and first molar teeth (teeth #19 and 21), prepared for a three‐unit all‐ceramic FDP. Impressions of the reference model were obtained using four impression systems (n = 10), group 1 (PVS impression scan), group 2 (stone cast scan), group 3 (Cadent iTero), and group 4 (Lava True Defintion). Then the three‐unit zirconia FDPs were milled. Marginal adaptation of the zirconia FDPs was evaluated using an optical comparator at four points on each abutment. The mean (SD) was reported for each group. One‐way ANOVA was used to assess the statistical significance of the results, with post hoc tests conducted via Tukey's HSD. p < 0.05 was considered statistically significant. All analyses were done using SPSS 22.0. Results: The mean (SD) marginal gaps for the recorded data from highest to lowest were silicone impression scans 81.4 μm (6.8), Cadent iTero scan 62.4 μm (5.0), master cast scan 50.2 μm (6.1), and Lava True definition scan 26.6 μm (4.7). One‐way ANOVA revealed significant differences ( p < 0.001) in the mean marginal gap among the groups. The Tukey's HSD tests demonstrated that the differences between all groups (silicone impression scan, master cast scan, Lava True definition scan, iTero Cadent scan) were statistically significant (all p < 0.001). On the basis of the criterion of 120 μm as the limit of clinical acceptance, all marginal discrepancy values of all groups were clinically acceptable. Conclusions: Within the confines of this in vitro study, it can be concluded that the marginal gap of all impression techniques was within the acceptable clinical limit (120 μm). Group 4 (Lava True Defintion) showed the lowest average gap among all groups followed by group 2 (stone cast scan), group 3 (Cadent iTero), and group 1 (PVS impression scan); these differences were statistically significant.